Elaboración del diagnóstico del grado de madurez en gestión de portafolio de las organizaciones del grupo de interés de PMO de Bogotá - Gil Chaparro, Daniel Alexander; Ojeda Mesa, Sergio Fernando; Rodriguez Silva, Nelson Armando (Escuela Colombiana de Ingeniería Julio Garavito, 2016)
This research aims to diagnose the portfolio maturity level of the organizations among PMO interest group in Bogotá, Colombia. For this, the authors created de Portfolio Maturity Model MMGPf which was developed from the information recollected from standards for portfolio management and from portfolio, programs and project maturity models, aiming to obtain a model that is adapted to reality and need of organizations evaluated. The research is exploratory, qualitative and action-research designed. The maturity model developed consists of 5 levels of maturity, consisting of three pillars (Strategic Planning, Portfolio Management Areas of Knowledge and Organizational Enablers), which are applied through an interview of 15 open-ended questions and a questionnaire of 110 closed-ended questions with five answer choices.

El propósito de la presente investigación es realizar el diagnóstico del grado de madurez en gestión de portafolio de las organizaciones del grupo de interés de PMO de Bogotá, Colombia. Para esto los autores crearon el Modelo de Madurez en Gestión de Portafolio MMGPf a partir de estándares en gestión de portafolio y de modelos de madurez en gestión de portafolio, programas y proyectos buscando adaptar el modelo a las necesidades y realidad de las organizaciones evaluadas. La investigación es de carácter cualitativo exploratorio, con diseño tipo investigación – acción. El modelo de madurez desarrollado consta de 5 niveles de madurez, compuesto por tres pilares (Planeación Estratégica, Áreas de Conocimiento de Gestión de Portafolio y Habilitadores Organizacionales), los cuales son aplicados a través de una entrevista de 15 preguntas abiertas y un cuestionario de 110 preguntas cerradas con 5 opciones de respuesta.
Keywords: Gestión de portafolio; Diagnóstico; Modelo; Madurez; PMO; Portfolio management; Diagnosis; Maturity; Model